2022
DOI: 10.20986/resed.2022.3994/2022
|View full text |Cite
|
Sign up to set email alerts
|

Eficacia de la fisioterapia sobre la ansiedad y depresión en pacientes con dolor crónico: Una revisión sistemática.

Abstract: Eficacia de la fisioterapia sobre la ansiedad y depresión en pacientes con dolor crónico: una revisión sistemática Efficacy of physiotherapy on the anxiety and depression in patients with chronic pain: a systematic review

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…In a systematic review including 45 studies with 9751 participants with Long Covid, 22.1% reported anxiety and 14.9% reported depression, among the most prevalent symptoms 33 . Other systematic reviews found that therapeutic exercise is a means of reducing symptoms, such as anxiety and depression 34 . Therapeutic exercise was included in our personalized programme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a systematic review including 45 studies with 9751 participants with Long Covid, 22.1% reported anxiety and 14.9% reported depression, among the most prevalent symptoms 33 . Other systematic reviews found that therapeutic exercise is a means of reducing symptoms, such as anxiety and depression 34 . Therapeutic exercise was included in our personalized programme.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Other systematic reviews found that therapeutic exercise is a means of reducing symptoms, such as anxiety and depression. 34 Therapeutic exercise was included in our personalized programme.…”
Section: Discussionmentioning
confidence: 99%
“…The management of patients with pain can be complex and may require a multidisciplinary approach considering all the factors described above to provide safe and quality care [ 34 ]. Moreover, to alleviate their condition, sometimes patients may seek alternatives (e.g., physiotherapy, which has been shown to be effective [ 10 , 36 ], and coping strategies that may influence the monitoring of pain. Patients with shoulder pain, for example, reported different barriers and facilitators, such as: support, knowledge, time/daily routine, access to equipment, beliefs, expectations, motivation, therapeutic response, and influence of the clinician [ 37 ].…”
Section: Discussionmentioning
confidence: 99%